Discontinuity persistence as a key variable in caving: a three-dimensional numerical evaluation for a sublevel caving method - Montiel, E; Jelicic, V; Ha, J; Mahabadi, O; Lisjak, A; Hormazabal, E (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Discontinuity persistence influences and, in some cases, controls the strength and anisotropic behaviour of rock masses. In the context of caving methods, it affects deformation mechanisms, the direction of the caving propagation, and the geometry of the subsidence, while also participating in the release of energy, establishing a direct link with induced seismicity. Current geotechnical sampling techniques limit the quantification of discontinuity persistence, particularly in complex geological environments accessed primarily through a limited number of drillholes. This introduces inherent biases of structural recognition at depth, resulting in a truncated representation of persistence at the caving scale and directly affecting the conclusions of caveability analyses used for design. This paper presents a numerical comparative study in which discontinuity persistence is identified as a key variable in sublevel caving, starting with an evaluation of the extraction footprint based on Laubscher’s theoretical criteria, whose results revealed limitations in capturing the role of persistence in caving propagation. The analysis presents a comparative numerical modelling approach, incorporating continuum (finite difference method [FDM]), discontinuum (distinct element method [DEM]), and hybrid models (finite–discrete element method [FDEM]), with the objective of assessing the limitations inherent to each approach and advancing towards a more consistent representation of the process (including discrete fracture network). Numerical results obtained from the discontinuum and hybrid approaches (DEM and FDEM) showed that discontinuity persistence, even under conditions of uncertainty, significantly controls caving propagation. This observation can only be made by explicitly capturing the connectivity and failure mechanisms associated with discontinuity features that are not adequately represented by simplified theoretical or purely continuumbased approaches. The results presented in this paper confirm the need to consider discontinuity persistence not only as a theoretical concept, but as a practical input in the design of caving operations, particularly in scenarios where available structural information is limited and/or incomplete.
Keywords: sublevel caving